The health of workers in the global gig economy - Uttam Bajwa; Denise Gastaldo; Erica Di Ruggiero; Lilian Knorr (BMC, 2018)
Abstract Background The "gig" economy connects consumers with contractors (or workers) through online platform businesses to perform tasks (or "gigs"). This innovation in technology provides businesses and consumers access to low-cost, on-demand labour, but gig workers' experiences are more complex. They have access to very flexible, potentially autonomous work, but also deal with challenges caused by the nature of the work, its precariousness, and their relationships with the platform businesses. Workers in the Global North and South may also experience these challenges very differently. Based on our report "Towards an Understanding of Canadian Workers in the Global Gig Economy", we present a commentary on the implications of a globalized online platform labour market on the health of gig workers in Canada and globally. Main body Based on our scoping review of peer and grey literature, we categorized gig worker vulnerabilities in three ways: 1) occupational vulnerabilities, 2) precarity, and 3) platform-based vulnerabilities. Occupational vulnerabilities are connected to the work being performed (e.g. driving a car or computer work) and are not specific to platform labour. Precarity refers to the short-term, contingent nature of the work, characteristics that may be shared with other forms of work. Some examples of precariousness are lack of health insurance, collective bargaining, or career training and promotion. Finally, platform-based vulnerabilities are particular to the way platform labour is structured. These vulnerabilities include worker misclassification, information asymmetries, and the culture of surveillance. We suggest that, together, these vulnerabilities challenge gig workers' right to health. Conclusions We propose that the experience of gig workers around the world must be understood in the context of neoliberalism, which has increased both the globalization and precaritization of work. While gig workers share some vulnerabilities, which have important negative consequences on their health, with other workers, the platform-specific vulnerabilities of workers require further inquiry. In particular, the specific health and overall experience of gig workers in different regions of the world - with different labour policies and sociopolitical contexts for work - must be disentangled as workers in the Global North and South experience this work very differently.